2021
DOI: 10.3390/biomedicines10010055
|View full text |Cite
|
Sign up to set email alerts
|

Differential iNKT and T Cells Activation in Non-Alcoholic Fatty Liver Disease and Drug-Induced Liver Injury

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) and idiosyncratic drug-induced liver injury (DILI) could share molecular mechanisms involving the immune system. We aimed to identify activation immunological biomarkers in invariant natural killer T (iNKT) and CD4/CD8+ T cells in NAFLD and DILI. Methods: We analyzed the activation profile (CD69, CD25, and HLA-DR) and natural killer group 2 member D (NKG2D) on iNKT cells, and CD4/CD8 T cells in peripheral blood mononuclear cells from NAFLD, with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Scholars have analyzed the activation profiles of iNKT cells, natural killer gene 2 members, and CD 4 /CD 8 T cells in peripheral blood mononuclear cells of NAFLD patients and DILI patients with or without significant liver fibrosis. CD 8 T cells were identified as a potential biomarker for distinguishing between liver fibrosis and MAFLD (13). In addition, animal experiments have found that CD 8 T lymphocytes exhibit a decrease in CD 25 activation markers under the action of co-stimulatory molecules expressed in dendritic cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have analyzed the activation profiles of iNKT cells, natural killer gene 2 members, and CD 4 /CD 8 T cells in peripheral blood mononuclear cells of NAFLD patients and DILI patients with or without significant liver fibrosis. CD 8 T cells were identified as a potential biomarker for distinguishing between liver fibrosis and MAFLD (13). In addition, animal experiments have found that CD 8 T lymphocytes exhibit a decrease in CD 25 activation markers under the action of co-stimulatory molecules expressed in dendritic cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…Other potential biomarkers for DILI are glutamate dehydrogenase, high mobility group protein B1, and macrophage colony-stimulating factor receptor; however further studies are needed for the validation of these markers [3]. Finally, a recent prospective cohort study has identified several protein biomarkers that could be useful to diagnose and distinguish DILI from any other acute liver injury in clinical practice, with fructose-1,6-bisphosphatase 1 being of particular interest [78].…”
Section: New Biomarkersmentioning
confidence: 99%
“…Therefore, immunophenotyping of patients at the time of liver injury would be useful to unravel the pathogenetic details of liver toxicity and to stop using empiric aggressive therapies (such as corticosteroids or alternative immune regulatory agents, when hepatotoxicity is unresponsive to oral steroids) to mitigate these adverse events. Subsequently, our group published another study [32] on extended immunophenotyping of DILI and MAFLD, focusing particularly on the iNK-T population. The highest level of iNK-T was found in PBMCs from MAFLD patients with significant liver fibrosis, suggesting a role for iNK-T in MAFLD progression.…”
Section: Immunophenotyping In Dili Blood Immunophenotyping Of Dilimentioning
confidence: 99%